2022
DOI: 10.1186/s12909-022-03525-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection control education for medical students undergoing clinical clerkship: a mixed-method approach

Abstract: Background Coronavirus disease (COVID-19) has induced an urgent need to train medical students not only in infection prevention control but also in the treatment of infectious diseases, including COVID-19. This study evaluates the impact of simulated clinical practice with peer role-plays and a lecture on clinical education for COVID-19. Methods The sample for the study included 82 fourth- and fifth-year medical students undergoing clinical clerksh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, peer teaching has been effective in EBM education [ 25 ]. In this study, in addition to the lecture on literature search conducted in our previous report [ 13 ], the program included activities that trained medical students to formulate clinical questions, critically review the literature examined, and reflect on their assigned patients. Peer reviews were also conducted, in which students shared the literature they examined and identified areas for improvement in their critical-thinking ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, peer teaching has been effective in EBM education [ 25 ]. In this study, in addition to the lecture on literature search conducted in our previous report [ 13 ], the program included activities that trained medical students to formulate clinical questions, critically review the literature examined, and reflect on their assigned patients. Peer reviews were also conducted, in which students shared the literature they examined and identified areas for improvement in their critical-thinking ability.…”
Section: Discussionmentioning
confidence: 99%
“…In our lecture for clerkship students in respiratory medicine held in 2019 [ 13 ], we showed that lectures on literature search during CC, where medical students needed to solve clinical questions, could be effective in improving literature search literacy. However, our previous report only focused on literature search during CC, while other elements of the five steps of EBM were not adequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…While infectious disease-prevention simulation programs have been developed for healthcare professionals since the outbreak of COVID-19 [20][21][22], they could not be implemented practically when caring for patients with infectious diseases, as the developed program was not diverse and the target audience was limited [4,20,23,24]. During the pandemic, we examined cases of applying electronic devices to infection management-related simulations, comparing them based on different situations and variables.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, we examined cases of applying electronic devices to infection management-related simulations, comparing them based on different situations and variables. However, comparing them across countries and devices was challenging owing to differing circumstances, and we plan to consider this aspect in future research [4,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%